Young People’s Attitudes to Attractive Work, During and After Upper Secondary School - Andersson, Ing-Marie; Gunnarsson, Kristina; Hedlund, Ann; Rosén, Gunnar (Nordic Journal of Working Life Studies, 2017)
Attractive work has been defined as a job position which an individual wants, where the employee experiences job stability and where employee identification and dedication are fostered. The present study is aimed at increasing knowledge about attitude changes to work during young people’s transition from school to work-life. A closed cohort, consisting of 225 pupils from graduating classes in 10 upper secondary schools in Sweden, was studied. The most significant result was found in the pupils’ expectations regarding work attractiveness while they were still attending school and in the subsequent year, after they had finished school. During school attendance, there were no differences between the groups, while those who did not find employment after school greatly reduced their demands regarding attractive work.Those who managed to get a job maintained the same level of expectation as during their school years, in terms of requirements for an attractive job.